Boris Klimychev’s Marquis de Tomsk – an Attempt to Define the Genre - Karpiński, Adam (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2015)
The author of the paper attempts to define the genre of the novel Marquis de Tomsk by Boris Klimychev, a modern (1930-2013) Russian writer from Siberia. His book has not been translated into Polish but neither is Klimychev well known in Russia, his work remaining known mostly to local readers. In the paper an essential emphasis has been placed on the literary analysis of genre characteristics of Klimychev’s romance. Marquis de Tomsk proves extremely difficult to describe because it combines the features of several literary genres. The analysis shows that the writer included in his book elements of historical novel, adventure novel and picaresque romance. He also used techniques and themes typical of the poetics of sentimentality. The plot centres on a series of episodes from the life of the characters, both such that have their historical prototypes and fictional ones. The writer relied on historical sources but also described in the novel interesting characters and events, taking into account their attractiveness to potential recipients. Klimychev foregrounded adventurous stories and made love intrigue an important element of the plot. All these components allow us to conclude that the book under discussion is a historical novel with features of picaresque romance.